ANALISIS VARIABILITAS CURAH HUJAN WILAYAH INDONESIA BERDASARKAN PENGAMATAN TAHUN 1975-2004 - Juaeni, Ina (MATEMATIKA, 2006)
Tropical rainfall is the most important atmospheric variable, because it can be affect directly to human life. Tropical rainfall is also important for global climate and weather. The annual total of tropical rainfall differs from year to year and from place to place. Other characteristics, such as its seasonal and diurnal distribution, intensity, and duration also demonstrate spatial and temporal variations. Results of the statistical analysis to rainfall data indicate that rainfall variation coefficients in the southern Indonesia are higher than its in the northern Indonesia .